Versatile asymmetric separator with dendrite-free alloy anode enables high-performance Li-S batteries - Yan, Wenqi (2023)
Lithium-sulfur batteries (LSBs) with extremely-high theoretical energy density (2600 Wh kg-1 ) are deemed to be the most likely energy storage system to be commercialized. However, the polysulfides shuttling and lithium (Li) metal anode failure in LSBs limit its further commercialization. Herein, a versatile asymmetric separator and a Li-rich lithium-magnesium (Li-Mg) alloy anode are applied in LSBs. The asymmetric separator is consisted of lithiated-sulfonated porous organic polymer (SPOP-Li) and Li6.75 La3 Zr1.75 Nb0.25 O12 (LLZNO) layers toward the cathode and anode, respectively. SPOP-Li serves as a polysulfides barrier and Li-ion conductor, while the LLZNO functions as an "ion redistributor". Combining with a stable Li-Mg alloy anode, the symmetric cell achieves 5300 h of Li stripping/plating and the modified LSBs exhibit a long lifespan with an ultralow fading rate of 0.03% per cycle for over 1000 cycles at 5 C. Impressively, even under a high-sulfur-loading (6.1 mg cm-2 ), an area capacity of 4.34 mAh cm-2 after 100 cycles can still be maintained, demonstrating high potential for practical application.